2019
DOI: 10.1144/petgeo2018-125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of basin architecture on diagenesis and dolomitization in a fault-bounded carbonate platform: outcrop analogue of a pre-salt carbonate reservoir, Red Sea rift, NW Saudi Arabia

Abstract: The early Miocene Wadi Waqb carbonate in the Midyan Peninsula, NE Red Sea is of great interest not only because of its importance as an archive of one of the few pre-salt synrift carbonate platforms in the world, but also as a major hydrocarbon reservoir. Despite this importance, little is known about the diagenesis and heterogeneity of this succession. This study uses petrographical, elemental chemistry, stable isotope (δ13C and δ18O) and clumped isotope (Δ47) analyses to decipher the controlling processes be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Recent studies have shown that the convection of seawater along fault planes and basal clastic aquifers can explain the formation of fault‐related dolomite from hydrothermal fluids (Martin‐Martin et al ., ; Hollis et al ., ; Al‐Ramadan et al, ). These models require that faults are open to the sea floor, as often occurs within extensional basins (Hollis et al ., ; Hirani et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the convection of seawater along fault planes and basal clastic aquifers can explain the formation of fault‐related dolomite from hydrothermal fluids (Martin‐Martin et al ., ; Hollis et al ., ; Al‐Ramadan et al, ). These models require that faults are open to the sea floor, as often occurs within extensional basins (Hollis et al ., ; Hirani et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the subsurface reservoir involves multi-scale and -dimensional analyzes, from one-dimensional borehole analysis (well log and core samples) to threedimensional depositional and property modeling (Amel et al, 2015;Al-Ramadan et al, 2020;Anees et al, 2022b;Anees et al, 2022a). In such cases, the classification and interpretation of lithofacies play a key role in providing the basic building block to a more advanced interpretation.…”
Section: Core-based Lithofacies Analysismentioning
confidence: 99%
“…In addition, the 54 carbon and oxygen isotopic data points from Miocene carbonate situated in the Midyan Peninsula at four different locations, Wadi Waqb, Ad-Dubaybah, Wadi Hamd, and Magna, were re-visited in this study (Al-Ramadan, 2017;Al-Ramadan et al, 2019).…”
Section: Site and Samplesmentioning
confidence: 99%
“…The Miocene carbonate in the Red Sea Basin is an ideal location for studying paleo-fluid circulation along fractures, due to of the exposed carbonate outcrop and the existence of a network of fractures filled with diagenetic calcite crystals (Al-Ramadan, 2017;Hollis et al, 2017;Al-Ramadan et al, 2019). Carbonate rocks are of particular interest, due to the wide variety of diagenetic modifications that can occur as a result of paleofluid circulation along fractures (Stacey et al, 2021a;Stacey et al, 2021b;Koeshidayatullah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%